The Effect of Work Environment on Work Stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection) - Meidy Sriska; Risa Kartika Lubis (Junal Ilmu Manajemen, 2020)
This study aims to determine the effect of the work environment on work stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection). The sample used in this study were employees at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection), the number of samples is 35 people. The results of this study indicate that the independent variable, namely the work environment factor (X) has a positive and significant effect on employee work stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection).